(untitled) (Research, Society and Development, 2023)
Purpose: The aim of this study was to estimate skeletal muscle mass in patients with gastroesophageal cancer. Methods: A cross-sectional study was conducted with male and female patients with gastroesophageal cancer in treatment at the Pernambuco Cancer Hospital in 2015. Data on socioeconomic, lifestyle, clinical, eating and anthropometric [body mass index (BMI) characteristics as well as percentage of weight loss (%WL)] were evaluated. Skeletal muscle mass (SMM) and the muscle mass index (MMI) were calculated. Results: One hundred patients participated in the study (62% male; mean age: 58.30 ± 10.90 years). Gastric cancer was more prevalent (61%), followed by esophageal cancer (24%). Based on the BMI, 30% were underweight and 71% had a severe %WL. SMM was 22.69 ± 6.02 kg, which is lower than that of healthy adults and elderly individuals. SMM was low in elderly individuals, females, those who did not use alcohol and those with a low BMI. Type of cancer was not associated with either SMM or the MMI. Conclusion: In the sample studied, skeletal muscle mass was lower than that found in healthy adults and elderly individuals and was associated with anthropometric variables, sex, age and lifestyle. A high rate of malnutrition was found, as evidenced by the percentage of weight loss.